Menigkatkan Nilai Ekonomi: Edukasi Pemanfaatan Limbah Kerang Menjadi Kerajinan Tangan - Hidayat, Nurul; Kasmin, Ichelia; Mayorah, Elsa; Muhti, Fahrul Ilham; Seda, Fansiskus; Thong, Hansen; Naila, Juwita; Peren, Uliperdi (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
Community Service activities are a real form of students' social concern for their surroundings. This activity was carried out in Kampung Enam with the aim of sharing knowledge and skills with the community and students about how to turn seashell waste into handmade crafts that can be sold. We used a face-to-face approach through socialization and training, one of which was making wall decorations in the shape of flowers. Besides involving the local people, students also took part in this activity so they could develop economic independence. The results showed that seashell waste has promising potential, both economically and socially, especially if developed into small environmentally friendly businesses. Hopefully, activities like this can continue and become an example of how to develop local crafts and increase the income of the people around Kampung Enam, Tarakan.